TAXONOMIC DOCUMENTATION OF COLEOPTERAN PHOTOTACTIC INSECT FAUNA OF RICE COLLECTED IN LIGHT TRAP AT JABALPUR DISTRICT OF MADHYA PRADESH, INDIA - Kurmi, Anil; Pachori, R.; Bhowmick, A. K.; Sharma, A. K.; Sharma, H. L.; Namdev, Brajesh K. (Innovative Farming, 2021)
The present research work was carried out at two distinct locations (Research Field and Farmer’s Field). The Research Field, Jawaharlal Nehru Krishi Vishwa Vidyalaya and Farmer’s Field Village – Jatwa, Panagar Block of district Jabalpur Madhya Pradeshduring two cropping season of rice i.e. Kharif of 2015 and 2016. Light trap was used for the taxonomic documentation Coleopteran phototactic insect fauna. Total 34 species of order Coleoptera belongs to 8 families were collected from rice ecosystem. Family Carabidae was the dominating family among the all 8 families. 34 species were collected at Farmer’s Field while 29 species at Research Field.